Predictive value of proliferating cell nuclear antigen index in response to interferon treatment in patients with chronic viral hepatitis B and C - Zeki KARASU; Funda YILMAZ; Galip ERSÖZ; Fulya GÜNŞAR; Yücel BATUR; Ulus Salih AKARCA (Turkish Journal of Gastroenterology, 2019)
-